Features of the narrative «Covid-19» in the German quality and mass press - A. I. Milostivaya (Гуманитарные и юридические исследования)
The article is devoted to the analysis of strategies for shaping public opinion, manifested at the linguistic level of mass media communication, in the narrative about COVID-19 from the German high-quality and mass press. The relevance of the study is due to the social relevance of a narrative analysis of the persuasive impact of the media during the COVID-19 pandemic, during which, through the prism of the relationship with coronavirus infection, the socio-political and economic problems of a state are brought to the fore in the high-quality and mass press. At the same time, the author’s special research interest is focused on the interpretation of frame models of authentic denotative situations in comparison with their interpretations in high-quality and mass German newspapers, which made it possible to characterize the axiological attitude of the subjects of narrative in the media to cognitive-discursive events in the geopolitical space not only in Germany and The European Union, but also the global world as a whole. The scientific novelty of the article is due to the fact that it is the first to characterize the persuasive impact of language strategies for shaping public opinion during the narrative of the coronavirus pandemic in the German high-quality and mass press in a comparative way. This article is based on the hypothesis of the correlation between factual information selection and its axiological interpretation by the subject of a communicative action in the journalistic newspaper narrative on the COVID-19, which takes place in both high-quality and mass press. Therefore, when studying strategies for shaping public opinion in the narrative on the pandemic, it is relevant to analyze the linguistic and logicalsemantic ways of denotative news content presenting. The main method for studying empirical material in this article is a frame analysis of the relationship between the prototypical described denotative situation and its textual representation in the narrative from the high-quality and mass press, which also indicates the scientific novelty of this study. At the same time, the attention of the researcher was focused on the interpretation of the asymmetry of the above phenomena as an axiologically marked constant, symmetry as an axiologically neutral interpretation of information and dissymmetry as a semi-marked case in terms of persuasive influence.